PARK13 regulates PINK1 and subcellular relocation patterns under oxidative stress in neurons. Issue 9 (2nd May 2014) - Patil, Ketan S.; Basak, Indranil; Lee, Sungsu; Abdullah, Rashed; Larsen, Jan Petter; Møller, Simon Geir
<x xml:space="preserve">Abstract</x> Parkinson's disease (PD) is a progressive and irreversible neurodegenerative disorder coupled to selective degeneration of dopamine‐producing neurons in the substantia nigra. The majority of PD incidents are sporadic, but monogenic cases account for 5–10% of cases. Mutations in PINK1 cause autosomal recessive forms of early‐onset PD, and PINK1 stimulates Omi/HtrA2/PARK13 protease activity when both proteins act as neuroprotective components in the same stress pathway. Studies on PINK1 and PARK13 have concentrated on phosphorylation‐dependent PINK1‐mediated activation of PARK13 and mitochondrial functions, because both proteins are classically viewed as mitochondrial. Although PARK13‐mediated protective mechanisms are at least in part regulated by PINK1, little is known concerning how these two proteins are regulated in different subcellular compartments or, indeed, the influence of PARK13 on PINK1 characteristics. We show that PARK13 localizes to a variety of subcellular locations in neuronal cells and that PINK1, although more restrictive, also localizes to locations other than those previously reported. We demonstrate that PARK13 accumulation leads to a concomitant accumulation of PINK1 and that the increase in PINK1 levels is compartmental specific, indicating a correlative relationship between the two proteins. Moreover, we show that PARK13 and PINK1 protein levels accumulate in response to H2O2 and L‐DOPA treatments in a subcellular fashion and that both proteins show relocation to the cytoskeleton in response to H2O2. This H2O2‐mediated relocation is abolished by PARK13 overexpression. This study shows that PARK13 and PINK1 are subcellular‐specific, but dynamic, proteins with a reciprocal molecular relationship providing new insight into the complexity of PD. © 2014 Wiley Periodicals, Inc.